PERALIHAN TANAH MELALUI JUAL BELI MENURUT HUKUM PERTANAHAN DI INDONESIA - Abdullah, Abdullah; Kurniawan, Itok Dwi (Prodi PPKn Universitas Slamet Riyadi, 2024)
Land is the embodiment of the existence and territory of each individual and each country. because people understand that Indonesia is an agricultural country and agriculture is one of the sources of livelihood of Indonesian people. Land is a source of livelihood for many people and should be specially protected by the state. This study aims to identify land transfer activities based on land law in Indonesia. This study uses normative legal research methods, through statutory and conceptual approaches. In the results and discussion of this study, the transfer of land use rights under national land law also refers to customary law. The transfer of land use rights in the form of purchase and sale is carried out on the basis of specific customary law and in money.